2023
DOI: 10.1017/pds.2023.132
|View full text |Cite
|
Sign up to set email alerts
|

Design Sprint: Use of Design Methods and Technologies

Iris Huić,
Nikola Horvat,
Stanko Škec

Abstract: This paper analyses the use of design methods and information and communication technology (ICTs) tools in design sprint (DS) activities. Team members, team leaders, and coaches of five international student teams were interviewed (40 interviews in total) regarding their use of design methods and ICT tools during three DS activities: problem definition, conceptual design, and embodiment design. The results show that teams utilise various methods through three approaches: one method for the task, several method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Namely, the observed teams received higher grades despite having larger proportions of Browsing actions compared to lower-graded teams. Moreover, the notable variability in Browsing actions among the teams could be attributed to the organization of CAD activities within design sprints, where teams usually divide themselves into sub-teams (Huić et al, 2023). Furthermore, in terms of CAD actions concerning the action type within the design sprint format, the study found a series of insights that both corroborate and diverge from the existing literature on collaborative CAD usage.…”
Section: Team-wise Cad Usagementioning
confidence: 53%
See 4 more Smart Citations
“…Namely, the observed teams received higher grades despite having larger proportions of Browsing actions compared to lower-graded teams. Moreover, the notable variability in Browsing actions among the teams could be attributed to the organization of CAD activities within design sprints, where teams usually divide themselves into sub-teams (Huić et al, 2023). Furthermore, in terms of CAD actions concerning the action type within the design sprint format, the study found a series of insights that both corroborate and diverge from the existing literature on collaborative CAD usage.…”
Section: Team-wise Cad Usagementioning
confidence: 53%
“…Furthermore, concerning PBL and CAD usage, particularly in the context of design sprints, there has been limited research on CAD activities. Huić et al (2023) studied four teams engaged in a one-day design sprint focused on CAD virtual prototyping tasks. Despite working in a co-located setting and utilizing collaborative synchronous CAD, the study revealed that teams typically organized themselves into subteams and encountered technical challenges related to large CAD files.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations